Two Polyketides from a Co-culture of Two Marine-derived Fungal Strains - Kossuga, Miriam H.; Ferreira, Antonio G.; Sette, Lara D. [UNESP]; Berlinck, Roberto G. S. (Natural Products Inc, 2013)
Co-cultivation of the fungal strains Penicillium sp. Ma(M3)V and Trichoderma sp. Gc(M2)1 in malt 2% medium led to the production of two novel, unusual polyketides, (Z)-2-ethylhex-2-enedioic acid and (E)-4-oxo-2-propylideneoct-7-enoic acid. Analysis of spectroscopic data enabled the structure determination of both compounds.
Keywords: Co-culture; Mixed fermentation; Marine fungi; Polyketides